[PP.17.22] PRIMARY ALDOSTERONISM AND TWIN PREGNANCY WITH INTRAUTERINE DEATH OF ONE FOETUS: A CASE REPORT. (September 2017) - Ciric, J.; Ciric, J.; Stojanovic, M.; Beleslin, B.; Stojkovic, M.; Savic, S.; Nisic, T.; Zarkovic, M.
Abstract : Objective: Primary aldosteronism (PA) appears in 7.4% of all cases with secondary hypertension during the reproductive age range. Still, only one hundred cases of pregnancy in PA have been reported. The cause is early termination of pregnancy in PA due to hypertension and hypokalaemia or an under diagnosis of PA in pregnancy. Pregnancy is a state of hyperreninemic hyperaldosteronism. High progesterone blocks mineralocorticoid receptor leading to a significant increase of aldosterone. Plasma renin activity (PRA) rises even more due to oestrogen stimulation. So, the aldosterone: PRA ratio in pregnant women with PA is falsely negative. We present the patient with PA and twin pregnancy complicated by single foetal intrauterine death. Design and method: A 30-year-old woman was investigated due to resistant hypertension and borderline hypokalaemia. PRA was 0.2 ng/ml/h, and the lowest level of aldosterone during the infusion test was 120 ng/l. Magnetic resonance scan revealed 12 mm adenoma of the left adrenal gland. Soon after the investigation twin pregnancy was revealed. Blood pressure was well controlled on Methyldopa 4 × 250 mg. At 26 weeks of pregnancy her blood pressure rose to 170/110 mmHg and proteinuria appeared. Pregnancy was complicated by single foetal intrauterine death. Results: At 37th week of gestation a dead foetus was delivered by caesarean section due to preeclampsia, and the other one died postpartum. She recovered completely and two years later decided for pre-conception surgery. The pre-treatment lowest level of aldosterone in the infusion test was 320 ng/l. Histopathology confirmed primary aldosteronism. The optimal management of PA during pregnancy requires an experienced team since there is a high risk of adverse outcomes. A reasonable approach is antihypertensives known to be safe in first trimester, considering amiloride in second and third trimester where hypertension or hypokalaemia is difficult to control. Twin pregnancy was the additional risk factor in this case, and a death of co-twin jeopardized maternal and neonatal outcome of the surviving foetus. Conclusions: Primary aldosteronism should be considered in all women with hypertension prior to conception or during pregnancy, especially where adrenal adenoma, hypokalaemia or proteinuria is present.